USAR: um modelo preditivo para avaliação da acessibilidade em tecnologias assistivas baseadas em realidade aumentada - Cedro, Carlos Costa (2015)
Currently about 15% of the world population has some type of disability. For these people the use of assistive technologies is essential. Augmented reality emerges as an important alternative to the creation of new assistive technologies, due to its numerous forms of participant tracking, which, if combined, can provide new possibilities for interaction. However, the use of augmented reality in the context of assistive technology is not a panacea, as each disability is unique, as well as each person has its own peculiarities. Therefore, it is important to analyze the accessibility of these applications, to ensure the benefit of its use effectively. This work proposes a predictive evaluation model, based on universal design and ISO 9241-171 standard. This model is able to evaluate the accessibility of augmented reality applications, when used as assistive technologies. The evaluation process consists of completing questionnaires, composed of clear and intelligible issues, so that they can meet the multidisciplinary public, without requiring any prior knowledge in evaluating accessibility. The product of evaluation made by questionnaires is a numerical indicator of accessibility, which represents the degree of compliance with accessibility requirements. The questions are sensitives to context, each questionnaire includes guidelines, which contains the minimum requirements of the participant, for each criteria, it is thus possible to obtain a holistic view of the evaluation, which can be customized for each participant or generalized to a specific disability. The main objective of this work is to propose a predictive model for the evaluation of accessibility, serving special educators, developers and assistive technology consumers, as a criteria for the decision of use of augmented reality applications.